Growth Characteristics of Sahiwal x Zebu F1 Crossbred Cattle in Uganda - Babigumira, Brian M.; Nabukalu, Robinah G.; Masaba, Joseph K.; Egadu, George W.; Mulindwa, Henry; Oluka, James; Kugonza, Donald R. (International Journal of Livestock Research, 2018)
This study assessed the growth of Sahiwal x Zebu crossbreds under low input production conditions in Uganda. Primary data consisted monthly live body weights of 64 Sahiwal first filial generation (F1) crossbred calves born between 2013 and 2015. The herd was on pasture; water provided ad lib and routine control of ticks and worms done. The minimum, average and maximum birth weights for the herd were 15.0, 23.2+ 7.0 and 40.0 kg with a 13% heterotic effect. Birth weight was significantly (P< 0.05) affected by year of birth. Birth weight averages for male and female calves were 24.0+ 7.4 and 22.6+ 7.1 Kg. Average 300-day live body weights for the herd, male and female calves were 85.6, 84.8 and 86.3 kg. Birth weight significantly (P< 0.001) affected average daily gains (AGDs) of the herd. Positive average daily gain significantly (P< 0.05) peaked between 90 to 150 days-of-age. The study recommended targeted supplementary feeding from 90 days-of-age